Solution of third-order linear homogeneous fuzzy ordinary differential equations by Laplace transform method using the generalized Hukuhara differentiability concept (Journal of Pure and Applied Sciences (Science Forum), 2026)
This work considers the solution of third-order linear homogeneous fuzzy ordinary differential equations (FODEs) based on the fuzzy Laplace transform method under the  generalized Hukuhara differentiability concept. The results of the third-order linear homogeneous is established and tested on some existing biomathematical models. C++ code is used to test the accuracy of the method. Finally, a recommendation for further studies is made on the establishment of results for odd- and even-order FODEs.